Analysis of Modern Pathomorphological Data Obtained in Experimental Studies - Sultonova Lola Djahonkulovna (Zien Journals, 2023)
It is known that the factors determining radiosensitivity are complex and depend on the type of laboratory animals, their age, constitution, state of metabolic processes, dose and type of radiation. It is generally accepted that there is a threshold dose for most somatic effects below which no significant effects are observed. By increasing the dose, the level of the body's reaction increases. The distribution of radiation effects over time is of great importance. Studies have shown that the reaction of the mammalian organism to radiation can be considered as a sum of interrelated effects on all their organs and processes. Different types of hematopoietic cells show different sensitivity - erythroblasts are more radiosensitive than myelocytes, myelocytes, megakaryocytes, etc. The radiation-protective properties of bee venom have been studied in various ways.
Keywords: electromagnetic vibrations; X-rays and γ-rays; low of α- and β-particles